2009
DOI: 10.1051/0004-6361/200811046
|View full text |Cite
|
Sign up to set email alerts
|

Two-component jet simulations

Abstract: Context. Theoretical arguments along with observational data of YSO jets suggest the presence of two steady components: a disk wind type outflow needed to explain the observed high mass loss rates and a stellar wind type outflow probably accounting for the observed stellar spin down. Each component's contribution depends on the intrinsic physical properties of the YSO-disk system and its evolutionary stage. Aims. The main goal of this paper is to understand some of the basic features of the evolution, interact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 39 publications
3
46
0
Order By: Relevance
“…Recent simulations (Meliani et al 2006;Romanova et al 2009;Matsakos et al 2009;Fendt 2009) also show the interplay of mixing between the two components. Several authors, e.g.…”
Section: Stellar Jet Theorymentioning
confidence: 94%
See 4 more Smart Citations
“…Recent simulations (Meliani et al 2006;Romanova et al 2009;Matsakos et al 2009;Fendt 2009) also show the interplay of mixing between the two components. Several authors, e.g.…”
Section: Stellar Jet Theorymentioning
confidence: 94%
“…Though important to model, those outflows are not necessarily more important on the long-term duration compared to the continuous underlying steady flow, as suggested by Romanova et al (2009). Moreover, Matsakos et al (2009) have shown that the variability of the source does not destroy the continuous steady jet. Indeed, they use the first solution presented in this paper, as initial condition for the inner spine jet of their simulations, but use a polytropic equation of state.…”
Section: Stellar Jet Theorymentioning
confidence: 97%
See 3 more Smart Citations